Exposure to English Before and After Entry into Head Start: Bilingual Children’s Receptive Language Growth in Spanish and English - Hammer, Carol Scheffner (Int J Biling Educ Biling, 2008)
This investigation examined the Spanish and English receptive vocabulary and language comprehension abilities of bilingual preschoolers who attended Head Start over a two-year period. It was hypothesised that bilingual children’s development would follow linear trajectories and that the development of children who were only exposed to Spanish in the home prior to school entry would differ from children with exposure to Spanish and English from birth. Results revealed that the two groups’ language abilities in Spanish and English differed at the beginning of the study as measured by raw and standard scores and that these differences were maintained over the two years. The exceptions to this were found in the children’s vocabulary abilities, with the difference between the two groups’ English standard scores narrowing over time and the difference between their Spanish standard scores increasing during the two-year period. Similar to research on monolingual and bilingual children with low socioeconomic status (SES), children’s development in both languages essentially followed linear trajectories. Children’s raw scores on the English receptive vocabulary test accelerated, similar to research findings on monolingual children of middle SES. Also, children’s standard scores on the Spanish language comprehension measure decelerated after an initial period of linear growth. Future directions for research are discussed.